2017
DOI: 10.4314/jasem.v20i4.20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the biochemical responses of catfish (<i>Clarias gariepinus</i> Burchell, 1822) after replacing fish oil with plant-based oils in their diets

Abstract: ABSTRACT:This study evaluated biochemical responses of Clarias gariepinus after replacing fish oil with plantbased oils in their diets. The sources of oils were coconut, olive, crude palm, sunflower and sesame seed. These oils were incorporated at 7% level to produce five isonitrogenous (41.03% protein) diets. The sixth diet contained fish oil and served as control experiment. Feeding trial was conducted in floating hapa (1m 3 ) system for 12 weeks. At harvest, blood samples were taken and examined for serum p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The Elasmobranchii, for instance, are known to use urea which is present in their blood in very large amounts to maintain the osmotic pressure of their blood approximately equal to that of their environment. In teleosts (such as tilapia), it has become a matter of interest to determine whether lipid type has any influence upon the concentration and distribution of their serum proteins [28]. The data presented in this study revealed that the concentrations of serum proteins were in normal range of between 6.0 to 8.0 g/dl which, indicated that the animals were apparently healthy throughout the experimental period.…”
Section: Discussionmentioning
confidence: 61%
“…The Elasmobranchii, for instance, are known to use urea which is present in their blood in very large amounts to maintain the osmotic pressure of their blood approximately equal to that of their environment. In teleosts (such as tilapia), it has become a matter of interest to determine whether lipid type has any influence upon the concentration and distribution of their serum proteins [28]. The data presented in this study revealed that the concentrations of serum proteins were in normal range of between 6.0 to 8.0 g/dl which, indicated that the animals were apparently healthy throughout the experimental period.…”
Section: Discussionmentioning
confidence: 61%
“…Numerous studies have shown that vegetable oils can substitute fish oil in fish diets without affecting fish growth. Indeed, palm oil (Ng et al 2003;Yilmaz et al 2004;Nyina-wamwiza et al 2007;Sotolu 2010;Effiong and Akpan 2016), sunflower oil (Ng et al 2003;Nyina-wamwiza et al 2007;Effiong and Akpan 2016), soya oil (Sotolu 2010), coconut oil (Aderolu and Akinremi 2009;Hammed et al 2014;Effiong and Akpan 2016), groundnut oil (Sotolu 2010), shea butter oil (Aderolu et al 2011), and olive and sesame oil (Effiong and Akpan 2016) have successfully been used in Clarias gariepinus diet. Nevertheless, they are not always available and become some time expensive.…”
mentioning
confidence: 99%